Pesantren as Social Capital for Regional Development: A Reflection on Kiai Leadership and Institutional Dynamics - Yenuri, Ali Ahmad; Nurseha, Ivan (Journal of Pesantren and Diniyah Studies, 2025)
Islamic boarding schools (pesantren) have significant potential as a source of social capital to support regional development; however, this role has not been fully integrated into regional development policies. This study aims to analyze the contribution of pesantren as social capital to regional development through the leadership of kiai and the pesantren's institutional dynamics. This research employs a qualitative approach, drawing on literature review and empirical reflection on the social practices of pesantren in various local contexts. Data were collected from scholarly literature, policy documents, and empirical experiences related to social and community empowerment activities conducted by pesantren. The results indicate that kiai leadership plays a crucial role in building social trust, strengthening community cohesion, and encouraging public participation, which constitute the core elements of pesantren social capital. Furthermore, adaptive institutional dynamics enable pesantren to contribute to human resource development, community economic empowerment, and the internalization of religious values and local wisdom in regional development processes. These findings demonstrate that pesantrens can serve as strategic partners for local governments in achieving inclusive and sustainable development. This study concludes that optimizing the role of pesantren as social capital requires stronger institutional recognition and systematic integration into regional development policies.